Effects of ricinoleic acid esters from castor oil of Ricinus communis on the vitellogenesis of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) ticks - Arnosti, Andre [UNESP]; Brienza, Paula Desjardins [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Chierice, Gilberto Orivaldo; Bechara, Gervasio Henrique [UNESP]; Calligaris, Izabela Braggiao [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
This study examines the effects of ricinoleic acid esters from Ricinus communis castor oil on the vitellogenesis of Rhipicephalus sanguineus ticks attached to hosts that were fed with commercial rabbit food containing these esters. The oocytes of ticks from the treatment group (TG) showed cytoplasmic changes that inhibited the development of oocytes I and II to the advanced stages (IV and V) in addition to preventing the maturation of oocytes V, resulting in small ones. In addition, sperm was not observed in ampoules. Our findings confirm the acaricide potential of ricinoleic acid esters. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus sanguineus; Vitellogenesis; Ricinoleic acid esters; Tick; Ricinus communis; Oocytes